Local communities in front of big external investors: an opportunity or a risk? - Angelo Antoci; Paolo Russu; Elisa Ticci (Fondazione Eni Enrico Mattei (FEEM), 2010)
In the current age of trade and financial openness, local economies in developing countries are becoming increasingly exposed to external investments. The objective of the proposed two-sector model with environmental externalities is to provide an insight into the interaction between external investors and local communities with a focus upon the different strategies and income sources available to each category. In this context, analysis suggests that environmental regulations and incentives offered in order to attract external capital investment (whether foreign or national) may have an un-uniform impact on the two typologies of actors.
Keywords: F21; F43; D62; O11; O13; O15; O41; Q20; 330; Foreign Direct Investments; Environmental Negative Externalities; Structural Changes; Poverty Alleviation